Immunotherapy for Pediatric Acute Lymphoblastic Leukemia: Recent Advances and Future Perspectives - Lv, Meng; Liu, Yan; Liu, Wei; Xing, Yabing; Zhang, Shengnan (Frontiers in Immunology, 2022)
Pediatric acute lymphoblastic leukemia (ALL) is the most common subtype of childhood leukemia, which is characterized by the abnormal proliferation and accumulation of immature lymphoid cell in the bone marrow. Although the long-term survival rate for pediatric ALL has made significant progress over years with the development of contemporary therapeutic regimens, patients are still suffered from relapse, leading to an unsatisfactory outcome. Since the immune system played an important role in the progression and relapse of ALL, immunotherapy including bispecific T-cell engagers and chimeric antigen receptor T cells has been demonstrated to be capable of enhancing the immune response in pediatric patients with refractory or relapsed B-cell ALL, and improving the cure rate of the disease and patients’ quality of life, thus receiving the authorization for market. Nevertheless, the resistance and toxicities associated with the current immunotherapy remains a huge challenge. Novel therapeutic options to overcome the above disadvantages should be further explored. In this review, we will thoroughly discuss the emerging immunotherapeutics for the treatment of pediatric ALL, as well as side-effects and new development.